Glycine reduces platelet aggregation - Schemmer, Peter; Zhong, Zhi; Galli, Uwe; Wheeler, Michael D.; Xiangli, Li; Bradford, Blair U.; Conzelmann, Lars Oliver; Forman, Dow; Boyer, José; Thurman, Ronald G. (Amino acids, 2013)
It has been demonstrated that a wide variety of white blood cells and macrophages (i.e. Kupffer cells, alveolar and peritoneal macrophages and neutrophils) contain glycine-gated chloride channels. Binding of glycine on the receptor stimulates Cl− influx causing membrane hyperpolarization that prevents agonist-induced influx of calcium. Since platelet-aggregation is calcium-dependent, this study was designed to test the hypothesis that glycine would inhibit platelet aggregation. Rats were fed diets rich of glycine for 5 days, while controls received isonitrogenous valine. The bleeding time and ADP- and collagen-induced platelet aggregation were measured. Dietary glycine significantly increased bleeding time about twofold compared to valine-treated controls. Furthermore, the amplitude of platelet aggregation stimulated with ADP or collagen was significantly decreased in whole blood drawn from rats fed 2.5 or 5 % dietary glycine by over 50 %. Addition of glycine in vitro (1-10 mM) also blunted rat platelet aggregation in a dose-dependent manner. Strychnine, a glycine receptor antagonist, abrogated the inhibitory effect of glycine on platelet-aggregation in vitro suggesting the glycine works via a glycine receptor. Glycine also blunted aggregation of human platelets. Further, the glycine receptor was detected in both rat and human platelets by western blotting. Based on these data, it is concluded that glycine prevents aggregation of platelets in a dose-dependent manner via mechanisms involving a glycine receptor.
Published online: 8 November 2012
Gesehen am 04.02.2022